Airway Management in Pan Facial Fracture: An Outcome Analysis of Elective Tracheostomy and Submental Endotracheal Intubation - Nair, Vipin Venugopal; Issar, Yuvraj; Singh Dhillon, Harmanjot; Singh Ghotra, Gurpinder; Pratap, Pranay; Mathur, Ayush; Singh, Kamalpreet (Lietuvos chirurgija, 2024)
Background and Aims. Pan facial fractures are complex and often requiring complex airway management. Elective tracheostomy (ET) and submental endotracheal intubation (SEI) are the two major techniques for airway management. The aim of this article is to compare the management outcome between these techniques. Methods. This study was done in a tertiary care hospital from Jan 2019 to Dec 2019. Data were retrieved for all patients from hospital admission-discharge reports, operation room records, follow-up notes, and clinical photograph records which was recorded prospectively after ethical clearance. Total 38 patients were included in the study after the exclusion criteria into two groups: submental endotracheal intubation (SEI) and elective tracheostomy (ET). Demographic data, intraoperative time (IOT), length of hospital stay (LOHS), postoperative pain score at three and seven days, and Vancouver Scar Score (VSS) at 4 and 12 weeks was compared between the two groups. Results. SEI consisted of 23 patients (60%) while ET had 15 (40%) patients. The mean age was 32.77±8.24 years in the SEI and 29.36±7.32 years in the ET. The IOT in SEI was 15.36±1.53 min and 24.60±1.40 min in the ET which was statistically significant (p = 0.00001). The LOHS was 11±3.87 days in SEI and 25.2±3.88 days in ET (p = 0.0001). The mean VSS at 4 and 12 weeks for SEI were moderate and mild respectively and for the ET was moderate and mild respectively. Both were statistically significant with a p = 0.003 and p = 0.006. Conclusion. Submental intubation is a safe airway management technique in pan facial fracture. It provides the surgeon with an excellent operative field for achieving the proper dental occlusion. Both short- and long-term outcomes are better compared to the alternative airway method of elective tracheostomy.